Case Report: Benign Uterine Adenomyoma Metastasis in the Right Lung - Zhang, Xiaowei; Jiang, Hongquan; Huang, Bifei; Wei, Hangping (Frontiers in Surgery, 2022)
Abstract Background: Pulmonary metastasis of benign uterine leiomyoma and uterine endometriosis has been reported; however, pulmonary benign metastasizing uterine adenomyoma has not been reported. Herein, we report the first case of pulmonary benign metastasizing uterine adenomyoma. It is very important to differentiate from pulmonary primary synovial sarcoma; histopathology and immunohistochemistry are very helpful. Molecular pathology can be used if necessary. Case presentation: A female patient was admitted to the hospital because of pulmonary nodules. Lung computed tomography (CT) showed a nodular high density shadow in the upper lobe of the right lung, with a clear boundary and a diameter of approximately 1.2 cm. The Contrast CT scan showed obvious enhancement, and no obvious lobulation or burr was found. Partial resection of the right upper pulmonary artery under Video-assisted thoracic surgery （VATS） was performed. Postoperative pathological report confirmed the lesion as metastatic benign adenomyoma of the right upper lung. Conclusion: Lung is the most common organ for malignant tumor metastasis, and a few benign tumors can also develop pulmonary metastasis. Pulmonary benign metastasizing adenomyoma is extremely rare, and the prognosis is very good after surgical resection. When pulmonary CT shows a solid high-density shadow, we should consider the possibility of a metastatic benign tumor.